(untitled) - Poltorak, Alexander (New York, 2002)
This book is the liveliest, best-written and most thorough introduction to the fundamentals of this subject. Yet it goes beyond the framework of basic IP protection to discuss emerging concepts as well as inside information immediately useful in the real world. In short, it forms the next rung in the advancement of IP management up the ladder from an art to a science.
Keywords: Intellectual property,Sở hữu trí tuệ; United States,Hoa Kỳ